FXS-Like Phenotype in Two Unrelated Patients Carrying a Methylated Premutation of the FMR1 Gene - Fernández, Esperanza; Gennaro, Elena; Pirozzi, Filomena; Baldo, Chiara; Forzano, Francesca; Turolla, Licia; Faravelli, Francesca; Gastaldo, Denise; Coviello, Domenico; Grasso, Marina; Bagni, Claudia (Frontiers in Genetics, 2018)
Fragile X syndrome (FXS) is mostly caused by two distinct events that occur in the FMR1 gene (Xq27.3): an expansion above 200 repeats of a CGG triplet located in the 5’UTR of the gene, and methylation of the cytosines located in the CpG islands upstream of the CGG repeats. Here, we describe two unrelated families with one FXS child and another sibling presenting mild intellectual disability and behavioural features evocative of FXS. Genetic characterization of the undiagnosed sibling revealed mosaicism in both the CGG expansion size and the methylation levels in the different tissues analysed. This report shows that in the same family, two siblings carrying different CGG repeats, one in the full-mutation range and the other in the premutation range, present methylation mosaicism and consequent decreased FMRP production leading to FXS and FXS-like features respectively. Decreased FMRP levels, more than the number of repeats seem to correlate with the severity of FXS clinical phenotypes